Minimally invasive resources for aesthetic correction of the nose. Case series (Research, Society and Development, 2025)
Correcting the aesthetics of the nose can be done through invasive or minimally invasive procedures. The objective of this case description was to present the aesthetic results of non-surgical nose reshaping performed with minimally invasive procedures, either combined or isolated, using hyaluronic acid fillers, botulinum toxin, and polydioxanone (PDO) threads, with a view to improving the appearance and self-esteem of patients with minor deformities in the nasal region. This series of cases describes protocols for combining minimally invasive interventions aimed at correcting the aesthetics of the nose, replacing surgical procedures. Hyaluronic acid fillers, polydioxanone filaments, and botulinum toxin were applied to strategic areas of the nose, allowing for aesthetic correction of the nasolabial angle, reduction of the hump, and improvement of alar closure. The results were favorable to the proposed aesthetic correction of the cases presented, which lasted for approximately 180 days. Based on the results, it is possible to suggest that the proposed protocols can be used for aesthetic correction of the nose.